PENGARUH PELATIHAN DAN PENGEMBANGAN PRESTASI KERJA KARYAWAN PADA PD. BPR BAPAS 69 MAGELANG - Muhdiyanto, Muhdiyanto; Wahyuanto, Afandy Wahyuanto (Universitas Muhammadiyah Magelang, 2005)
The title of this research is “Influence of Training and Development to Work performance of PD BPR BAPAS 69 Magelang”. The researcher choose this title because of the industrial condition of banking which progressively tighten in its competition, so that each bank need the skilled to analyze and solving proble faced. This improvement conducted through education, training and development that show the form of readiness to be more skilled and ecleric. Variable will investigate training and development as independent variable and work performance as dependent variable. The aim of this research wants to know the influence of training and development to work performance both partial and also simultaneous. The dates collected use the purposive sampling, the population about 150 people, while the samples are 50 people which have been to do the training management. Reseacher durig July-November 2006. Result of reseach indicate that the independent variable influence the dependent variable. The value of coefficient determination shows the value equal to 23,4%, the other equal to 76,6%. It’s mean the independent variable influences is 23,4%, 76,6% by another variable out of this models. By partial method, training does not have effect to work performance, while development has an effectt on to work performance. Development is dominant variable has effect to work performance of PD BPR BAPAS 69, employees. Recommendation for company should give an opportunity to the employees to more improve their potencies by education and training. Training suggested to give intensively to the employees, because the profesionalis. Through the training can be conduct to its work performance.